An Overview of Human Immunodeficiency Virus Test Outcomes in Public Health Center Services: An Overview of Human Immunodeficiency Virus Test Outcomes in Public Health Center Services - Tetrina Purtaria; Solikhah Solikhah; Sulistyawati Sulistyawati (Universitas Ahmad Dahlan, 2026)
Background : Human Immunodeficiency Virus (HIV) remains a significant global health challenge, with Indonesia identified as a high-vulnerability nation. This study describes HIV testing services and outcomes at community health center (PHCs) in Sleman District, Indonesia, as part of a national policy to eliminate HIV. Method : A descriptive study was conducted using data from the SIHA 2.1 system for all 941 patients who underwent HIV testing at Gamping Two PHC from January to December 2024. The analysis focused on testing volume, demographic characteristics, and positivity rates across different key populations and age groups. Results : Pregnant women constituted the largest group tested (514), largely due to mandatory antenatal screening, followed by the general population (124). The most frequently tested age group was 21-35 years (688 patients). Overall, 941 individuals were tested, with 8 new positive HIV diagnoses recorded. Notably, males accounted for 6 of the positive cases, primarily within the Men Who Have Sex with Men (MSM) population (aged 21-35 and 36-50 years), while two females tested positive, one from the pregnant women group (<20 years) and another from the Sexually Transmitted Infection (STI) group (21-35 years). Conclusion : These findings highlight the continued importance of PHC-based testing services in identifying HIV cases, particularly among key populations like MSM and pregnant women, underscoring the need for targeted prevention and intervention strategies.